The Violation of Cooperation Principles as a Means of Humor on the Vindes Youtube Channel - Helty, Helty; Sholiha, Mar’atun; Izar, Julisah; Pratiwi, Fahroza Suci (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2023)
This research aimed to analyze violations of the principle of cooperation in VINDES' speech with Tretan Muslim. The research data was the speeches in the VINDES discourse with Tretan Muslim which were uploaded on the VINDES YouTube channel on June 13 2022. This research used a descriptive qualitative approach. The data collection technique was carried out using a reading-note technique. The data analysis method used in this research is the matching method. In the matching method, the data analysis technique used the pragmatic matching technique. The pragmatic equivalent technique used to analyze forms of deviation from the principle of cooperation in VINDES' humorous utterances. The research results showed that the utterances in the VINDES discourse contain violations of the principle of cooperation, namely the maxim of quality 6 data, the maxim of quantity 2 data, the maxim of relevance 4 data, and the maxim of method/implementation1 data. The most frequently found violations were the maxim of quality. This was deliberately done to create a humorous effect and invite laughter from the audience.